Turn-on time delay characteristics of external cavity laser based polymer fiber gratings - Hisham, Hisham K.; Abas, Ahmad F.; Mahdi, Mohd A. (National Institute of Optoelectronics, 2023)
The turn-on time delay (TDelay) characteristics of an external cavity laser-based polymer fiber gratings (PFGs) is successfully investigated. Numerical optimization of model parameters is used to reduce the laser TDelay by analyzing the effects of the laser injection current (Iinj), the temperature (T) variation, the recombination rate R(N) coefficients, and the external OFB level on TDelay. Results show that the effect of R(N) coefficients are to increase the TDelay value and not decrease it as written in the previous studies. Also, results show that the TDelay value is increased when T is increased. However, we can eliminate it either by increasing the ² value (i.e.Ni Nth) at a fixed value of Iinj or by increasing the value (i.e.thIinj I) at constant Ith. In addition, we can use the external optical feedback (EOF) level as a controller for reducing the TDelay value or to turn-on the laser by controlling the Nth value depending on the EOF level.